1960 ile 1980 yılları arasında Türk otomotiv sektörünün gelişmesi - Altuğ, Mert (My University, 2010)
Otomotiv Tarihi, Yan Sanayi Gelişimi ÖZET 1960 ile 1980 YILLARI ARASI TÜRK OTOMOTİV SEKTÖRÜNÜN GELİŞMESİ Günümüzde Otomotiv sanayi, gerçekleştirmiş olduğu ihracat hacmi, yurtiçi üretim adetleri, geliştirmiş olduğu yan sanayi, sağlamış olduğu istihdam olanakları ile Türkiye sanayinin itici kuvveti haline gelmiştir. Bu çalışma günümüzde bu katma değere sahip olan sektörün global bazda nasıl doğduğunu, Türk otomotiv sanayindeki gelişmeleri, 1960’lardaki planlı dönemde geçirmiş olduğu değişimi ve bu gelişmelerin 1980’e kadar olan bölümü içerir. Ayrıca benzer ekonomik dönemlerden geçmiş olan Güney Kore otomotiv sanayisinin şu anki durumu ve Türk otomotiv sanayisiyle benzerlik ve farklılıkları değerlendirir. Automotive Industry of Turkey, Development of Supplier Industry

THE DEVELOPMENT OF THE TURKISH AUTOMOTIVE SECTOR BETWEEN 1960 AND 1980 Today the automotive industry, with its export volume, domestic manufacturers quantities, improved part manufacturers, supplied employment rates became the thrusting power of the Turkish industry. This study analyzes the birth of the improved sector in the global bases, improvements in the Turkish Automotive sector, the changes after the 1960’s planned programs and these improvements till the 1980’s. It evaluates the actual states in the automotive industry of the South Korean Automotive sector that has a similar economical history as Turkey. Also it shows the similarities and differences between the Turkish and the South Korean Automotive industries.
Keywords: Ekonomi; Otomotiv_Türkiye